Rosemary extract improves cognitive deficits in a rats model of repetitive mild traumatic brain injury associated with reduction of astrocytosis and neuronal degeneration in hippocampus. (27th May 2016) - Song, Hai; Xu, Lincheng; Zhang, Rongping; Cao, Zhenzhen; Zhang, Huan; Yang, Li; Guo, Zeyun; Qu, Yongqiang; Yu, Jianyun
Highlights: Repetitive mild traumatic brain injury caused spatial learning and memory deficits. This trauma caused increased astrocytosis and neuronal degeneration in hippocampus. Rosemary extract improves cognitive deficits. Rosemary extract caused decreased astrocytosis and neuronal degeneration in hippocampus. Abstract: In this study, we investigated whether Rosemary extract (RE) improved cognitive deficits in repetitive mild Traumatic brain injury (rmTBI) rats and its potential mechanisms. The present results showed that rmTBI caused cognitive deficits, such as increased latency to find platform and decreased time spent in target quadrant in Morris water maze (MWM). These behavioral alterations were accompanying with the increased neuronal degeneration and glial fibrillary acidic protein (GFAP)-positive cells, increased Reactive oxygen species (ROS) generation, decreased activity of Superoxide Dismutase (SOD), Glutathione Peroxidase (GPx) and Catalase (CAT), elevated protein level of IL-1β, IL-6 and TNF-α in hippocampus. Treatment with RE prevented these changes above. Our findings confirmed the effect of rosemary extract on improvement of cognitive deficits and suggested its mechanisms might be mediated by anti-oxidative and anti-inflammatory. Therefore, rosemary extract may be a potential treatment to improve cognitive deficits in rmTBI patients.